Persepsi Wanita Usia Subur tentang Pemilihan Kontrasepsi IUD - I Dewa Ayu Ketut Surinati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2015)
The purpose of this research is to know The description of the perception of women of childbearing age about the contraceptive IUD. The methode of this research was discriptif with cross sectional design. The samples were consisted of 50 respondents selected with Consecutive sampling technique. These results indicate that, of the 50 respondents, 66% of respondents have a positive perception.